The (Sizable) Role of Rehypothecation in the Shadow Banking System - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2010)
This paper examines the sizable role of rehypothecation in the shadow banking system. Rehypothecation is the practice that allows collateral posted by, say, a hedge fund to its prime broker to be used again as collateral by that prime broker for its own funding. In the United Kingdom, such use of a customer's assets by a prime broker can be for an unlimited amount of the customer's assets while in the United States rehypothecation is capped. Incorporating estimates for rehypothecation (and the associated re-use of collateral) in the recent crisis indicates that the collapse in non-bank funding to banks was sizable. We show that the shadow banking system was at least 50 percent bigger than documented so far. We also provide estimates from the hedge fund industry for the - churning - factor or re-use of collateral. From a policy angle, supervisors of large banks that report on a global consolidated basis may need to enhance their understanding of the off-balance sheet funding that these banks receive via rehypothecation from other jurisdictions.